A Comparative Study of the Mechanical Properties of Jute Fiber and Yarn Reinforced Concrete Composites. Issue 5 (3rd May 2020) - Zakaria, Mohammad; Ahmed, Mashud; Hoque, Mozammel; Shaid, Abu
ABSTRACT: A relatively better performance of jute fiber and yarn reinforced concrete composites can open up a wide access to application of natural resources in concrete strengthening. In order to achieve this goal, an experimental investigation on the flexural, compressive and tensile strengths of Jute Fiber Reinforced Concrete Composites (JFRCC) and Jute Yarn Reinforced Concrete Composites (JYRCC) has been conducted. To draw a specific conclusion, the mix ratios of 1:1.5:3 and 1:2:4 (by volume) of concrete have been maintained with incorporation of jute fiber and yarn in concrete mortar having different cut lengths with distinct volumetric ratios. Finally, a comparison of the JFRCC and JYRCC strength increments with respect to the plain concrete has been investigated. A significant increment of compressive, flexural and tensile strength was observed only for a short cut length having a low volumetric ratio, where JYRCC increment value was always found progressive. A far more regular arrangement and adequate mixture of JYRCC was also visualized compare to JFRCC in concrete mortar. All the principal increment values were found only in case of JYRCC with a mix ratio of 1:1.5:3. So, it can be concluded that the presence of jute yarn and more cement content can strengthen the concrete to a great extent.